Keeping the Game Alive: Evaluating Strategies for the Preservation of Console Video Games - Mark Guttenbrunner; Christoph Becker; Andreas Rauber (International Journal of Digital Curation, 2010)
Interactive fiction and video games are part of our cultural heritage. As original systems cease to work because of hardware and media failures, methods to preserve obsolete video games for future generations have to be developed. The public interest in early video games is high, as exhibitions, regular magazines on the topic and newspaper articles demonstrate. Moreover, games considered to be classic are rereleased for new generations of gaming hardware. However, with the rapid development of new computer systems, the way games look and are played changes constantly. When trying to preserve console video games one faces problems of classified development documentation, legal aspects and extracting the contents from original media like cartridges with special hardware. Furthermore, special controllers and non-digital items are used to extend the gaming experience making it difficult to preserve the look and feel of console video games.